I Serahen Ku Tengku-Guru Sebagai Model Komunikasi Edukatif Berbasis Kearifan Lokal di Dayah As-Sirajy Kabupaten Aceh Tengah - Auni, Luthfi; Johansyah, Johansyah (IAIN Takengon, 2022)
This study aims to determine the concept and application of Iserahen ku tengku-guru at Dayah As-Sirajy Central Aceh as a form of interpersonal communication. This research is a qualitative research with the type of phenomenological-naturalistic research. Based on the results of the study, it was found that Dayah As-sirajy Central Aceh made local wisdom one of the flagship programs. Various programs and activities in this dayah are correlated with the values of local wisdom, including in building educational communication. As for its implementation, this Dayah has tried to build communication with the parents of the students through the traditional ceremony of iserahen ku tengku-guru as a model of interpersonal communication since the beginning of students receiving education in this dayah. Furthermore, students' parents are active in tingok-sino, namely the process of monitoring the development of students. Likewise, the community and government agencies are also actively monitoring. The final stage of iulaken ku urangtue has not been carried out because no one has completed their education. Based on communication theory, Iserahen ku tengku guru is a form of educative communication based on local wisdom that is applied by this dayah